Coronavirus, god's message to man: who reads it? - Eid, Iyad Muhammad (The IIUM Covid19 Psychosocial Support Team, 2020)
There is no doubt that the universe moves within a precise, well-organized system that never derails, “Indeed, all things We created with predestination.” (Al-Qamar: 49). Certainly, covid-19 pandemic has been created with predestination, and it carries a message from its Creator to the inhabitants of the earth. “And never would your Lord have destroyed the cities until He had sent to their mother a messenger reciting to them Our verses. And We would not destroy the cities except while their people were wrongdoers.” (Al-Qasas: 59)